Silicon Application Increases Drought Tolerance of Kentucky Bluegrass by Improving Plant Water Relations and Morphophysiological Functions - Shah Saud; Xin Li; Yang Chen; Lu Zhang; Shah Fahad; Saddam Hussain; Arooj Sadiq; Yajun Chen (The Scientific World Journal)
Drought stress encumbers the growth of turfgrass principally by disrupting the plant-water relations and physiological functions. The present study was carried out to appraise the role of silicon (Si) in improving the drought tolerance in Kentucky bluegrass (Poa pratensis L.). Drought stress and four levels (0, 200, 400, and 800 mg L−1) of Si (Na2SiO3·9H2O) were imposed after 2 months old plants cultured under glasshouse conditions. Drought stress was found to decrease the photosynthesis, transpiration rate, stomatal conductance, leaf water content, relative growth rate, water use efficiency, and turf quality, but to increase in the root/shoot and leaf carbon/nitrogen ratio. Such physiological interferences, disturbances in plant water relations, and visually noticeable growth reductions in Kentucky bluegrass were significantly alleviated by the addition of Si after drought stress. For example, Si application at 400 mg L−1 significantly increased the net photosynthesis by 44%, leaf water contents by 33%, leaf green color by 42%, and turf quality by 44% after 20 days of drought stress. Si application proved beneficial in improving the performance of Kentucky bluegrass in the present study suggesting that manipulation of endogenous Si through genetic or biotechnological means may result in the development of drought resistance in grasses.